(18又(3/4)+(-2.75)+(2.125)+(+12又5/7)+(-4又1/8)
3个回答
原式=16-6+9+2+12又5/7
=33又5/7
相关问题
简便计算 0.75+(2又3/4)+(+0.125)+(-12又5/7)+(-4又1/8)
2-12/5-18/5+12/1-18/7-2又17/8=?-0.5-(-3又4/1)+2.75-(+7又2/1)=?
18又4分之3+(-2.75)+(2.125)+(12又7分之5)+(负4又8分之1)结果等于多少
0.75+(-2又4分之3)+0.125+12又7分之5+(-4又8分之1)等于多少
6-1又5/8= 1又4/5÷18= 0.18×5/6= 0.75-1/4= 4-1又1/3= 7÷2又1/3= 2又1
28又1/4+(-17又1/2)=多少? 0.75+(-11/4)+0.125+(-5/7)+(-4又1/8)=多少?
0.75+(-3又4/3)+(+0.125)+(8又-7/6)+(-3又8/1)=
(-4又1/8)-|-1+2+0.125|-|-3又1/3|-(-6又1/7)+(-5又1/7)
计算:(-2又3/4)+1又2/3+0.75+(+1/8)+(-3.125)
5/17*(-3/7)+5/17*(-4/7)-12/17 (-0.75)*(-3又1/8)-0.75*(-4又7/8)